An Ethics of Repair? Towards Reparative Principles in the History of Education - Keynes, Matthew R. (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2024)
Histories of education are closely entwined with agendas of reparative justice, redress and reconciliation. Educational questions, past and present, have been central to recent debates about redress, and historical thinking has a vital role to play in making sense of the afterlives of violence that are history’s present. This includes exposing the role of education in justifying human exceptionalism and legitimating violence as well as radically re-historicising educational pasts from entangled, decolonial, and post-anthropocentric perspectives, work that is already underway.This conceptual paper takes up these intersecting imperatives for repair and the revaluation of historical research in education. It asks: what might reparative histories of education look like? What might constitute an ethics of repair for the history of education?To address these questions, three principles concerned with the repair of past injustices are canvassed: complex implication, care and concern, and legibility. The goal is not to normatively prescribe or evaluate principles, but to explore how these are already informing some kinds of historical work, and to provoke dialogue about how we might develop reparative dimensions to our work in a world that desperately needs repair.